Surface Cracking of Bakli (Anogeissus latifolia) and Sal (Shorea robusta) during Drying - Kishen, Jai (Indian Forester, 1954)
In this paper the phenomenon of cracking of wood during drying is discussed in brief. The moisture gradient on the surface at the time of cracking of wood, called the critical moisture gradient, has been directly determined for bakli and sal. An attempt has been made to show how far the critical moisture gradient is dependent upon the maximum strain perpendicular to the grain and the coefficient of shrinkage. The importance of this investigation to the seasoning of refractory woods has also been touched upon in the paper.